Dukungan Keluarga dengan Keberhasilan Pemberian ASI Eksklusif - Margaretha Putri Sariningrum; Yuni Fitriana; Sri Susilowati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: Standard low of suckle on the breast in some countries because decrease of support breastfeeding for mother in around area. The problem often come at 2012, in global giving exclusive breastmilk still under50%. Family support for breastfeeding that know breastmilk good food for baby is better supported for successbreasfeeding. Study preface in Sidoarum Village mention one of factor about giving exclusive breastmilk is a familysupport.Goal: The goal of the research to know about the relation of family support with sucessful giving exclusive breastmilk in Sidoarum Village Godean Sleman 2016Method: This research is quantitative research, design with descriptive correlation, use cross sectional research.The subject of the study is mother who has baby between 6 to 11 month at February 2016. In selecting sample,its research use cluster random sampling with 48 respondents. It is analyzed by chi-square and the instrument isused questionnaireResult: The result from 48 responden family support at offer bresfeeding exclusive there are 26 respondent (54,2%).The mother was success give breastfeeding such as 38 responden (79,2%). There is any relation between familysupport with sucessful giving exclusive breastmilk (p-value=0.000).Conclusion: There is any relation between familly support to sucessful giving exclusive breastmilk in SidoarumVillage Godean Sleman 2016. The expect familly giving motivation mother for breasfeeding in order to sucessfulgiving exclusive breastmilkKeyword: Family Support, exclusive breastmilk.